Intestinal Region-Dependent Alterations of Toll-Like Receptor 4 Expression in Myenteric Neurons of Type 1 Diabetic Rats - Nikolett Bódi; Abigél Egyed-Kolumbán; Benita Onhausz; Bence Pál Barta; Afnan AL Doghmi; János Balázs; Zita Szalai; Mária Bagyánszki (Biomedicines, 2023)
Toll-like receptor 4 (TLR4) can activate pro-inflammatory cascades in the gastrointestinal tract. Our aim was to determine TLR4 expression in myenteric neurons of different gut regions using a type 1 diabetic model. Ten weeks after the onset of hyperglycemia, myenteric whole-mount preparations from the duodenum, ileum and colon of streptozotocin-induced diabetic, insulin-treated diabetic and control rats were prepared for TLR4/peripherin double-labelling fluorescent immunohistochemistry. Immunogold electron microscopy was applied to evaluate TLR4 expression in the myenteric perikaryon and neuropil. Tissue TLR4 levels were measured by enzyme-linked immunosorbent assay. In controls, the number and proportion of the TLR4-immunoreactive myenteric neurons showed an increasing tendency to aboral direction. These values were significantly higher in diabetics compared to controls in the duodenum and ileum, but were significantly lower in the colon. In diabetics, the distribution of TLR4-labelling gold particles between the perikaryon and neuropil of myenteric neurons varied in a different way by intestinal segment. TLR4 tissue concentration changed only in the diabetic duodenum, and it decreased in muscle/myenteric plexus-containing homogenates, while it increased in mucosa/submucosa/submucous plexus-containing samples relative to controls. Insulin had beneficial effects on TLR4 expression. These findings support that chronic hyperglycemia has segment-specific effects on TLR4 expression, contributing to gastrointestinal disorders in diabetic patients.